Solid pseudopapillary neoplasms of the pancreas are dependent on the Wnt pathway. Issue 8 (3rd July 2019) - Selenica, Pier; Raj, Nitya; Kumar, Rahul; Brown, David N.; Arqués, Oriol; Reidy, Diane; Klimstra, David; Snuderl, Matija; Serrano, Jonathan; Palmer, Héctor G.; Weigelt, Britta; Reis‐Filho, Jorge S.; et al.
Abstract : Solid pseudopapillary neoplasms (SPNs) are rare and relatively indolent tumors of the pancreas. While primary SPNs can be surgically resected, there are currently no therapies available for patients with advanced stage disease. Given that these tumors frequently carry CTNNB1 hotspot (recurrently mutated loci in a gene) mutations resulting in β‐catenin nuclear accumulation, it has been speculated that the Wnt pathway may be a driver in this disease. Here, we present a comprehensive "multi‐omics" study where the genome, transcriptome, and methylome of SPNs were analyzed. We found that SPNs are characterized by a low‐complexity genome where somatic mutations in CTNNB1, present in 100% of the cases, are the only actionable genomic lesions. Compared to more common subtypes of pancreatic tumors (adenocarcinomas and pancreatic neuroendocrine tumors), SPNs show high expression levels of genes belonging to the Wnt pathway. Their methylome was consistent with an epithelial cell origin and a general upregulation of Wnt pathway genes. Clinical studies to evaluate the exquisite sensitivity of SPNs to inhibitors of the Wnt pathway are warranted. Abstract : Solid pseudopapillary neoplasms of the pancreas are governed by the presence of mutations of β‐catenin that, in turn, induce transcriptional rewiring, which converges in the activation of the Wnt pathway and proliferation of tumor cells.